A highly efficient Francis turbine designed for energy recovery in cooling towers. (18th March 2015) - Zhou, Daqing; Chen, Huixiang; Yang, Chunxia
In China, cooling water entering cooling towers still retains surplus pressure between 39, 240 and 147, 150 Pa. In order to utilize this wasted energy, it is suggested that the surplus water energy can be harnessed to drive a type of hydroturbine installed in the inner platform of cooling tower and make the fan rotate via its coupled shafts. However, conventional hydroturbines are not suited for this job because of their low efficiency or unmatched rotating speed with that of the fan under the operating conditions of cooling towers. In this article, according to the requirements of turbine work environment in cooling towers, a new type of hydroturbine, Francis turbine with ultra-low specific speed ( ns  = 50 m.kW), was designed to replace the fan motor in a cooling tower. Primarily, the shape, position, and number of runner blades were designed and optimized through theoretical analyses and computational fluid dynamics simulations. Additionally, metal elliptical volute and single-row ring guide vanes were applied to scale down the structural dimensions. Finally, the optimal scheme of the new Francis turbine was proven to have a high efficiency of 88% and good operation stability through testing of a physical model and can achieve the goal of harvesting renewable energy in the cooling tower.